Effects of pH and microbial composition on odour in food waste composting - Sundberg, Cecilia (Pergamon Press, 2013)
A major problem for composting plants is odour emission. Slow decomposition during prolonged low-pH conditions is a frequent process problem in food waste composting. The aim was to investigate correlations between low pH, odour and microbial composition during food waste composting. Samples from laboratory composting experiments and two large scale composting plants were analysed for odour by olfactometry, as well as physico-chemical and microbial composition. There was large variation in odour, and samples clustered in two groups, one with low odour and high pH (above 6.5), the other with high odour and low pH (below 6.0). The low-odour samples were significantly drier, had lower nitrate and TVOC concentrations and no detectable organic acids. Samples of both groups were dominated by Bacillales or Actinobacteria, organisms which are often indicative of well-functioning composting processes, but the high-odour group DNA sequences were similar to those of anaerobic or facultatively anaerobic species, not to typical thermophilic composting species. High-odour samples also contained Lactobacteria and Clostridia, known to produce odorous substances. A proposed odour reduction strategy is to rapidly overcome the low pH phase, through high initial aeration rates and the use of additives such as recycled compost.